Determination of Physico-chemical Properties of Aonla (Emblica officinalis Gaerth) Fruits among Different Populations in Garhwal Himalaya. (21st September 2020) - Chandra Naithani, Dinesh; Rawat, J.M.S.; Singh, Bhupendra; Khanduri, Vinod Prasad; Riyal, Manoj Kumar
ABSTRACT: The present investigation was conducted to evaluate the variation in nutritive contents in wild-growing fruits of Emblica officinalis . Fruits of E. officinalis were collected from twenty-eight naturally growing populations in different parts of Garhwal-Himalaya, Uttarakhand, India. Several fruit properties including number of fruits kg −1, fruit weight, fruit diameter, fruit length, fruit volume, pulp weight, pulp:stone ratio, specific gravity, moisture percent, total soluble solid, malic acid, citric acid, tartaric acid, vitamin C, and sugar contents were analyzed to observe t he variations among different populations . The results of the study revealed that the average fruit weight varied significantly ( P < .05) from 2.70 to 13.61 g. Total soluble solids, malic acid, citric acid, tartaric acid, and vitamin C were found ranged between 10.68 and 21.42 °Brix; 1.43 and 3.78%; 1.37 and 3.61%; 3.21 and 8.46% and 191.13 and 495.21 mg 100 g 1, respectively ). Fruit weight was the most variable parameter among the physical characteristics. Vitamin C and organic acid contents were highly variable among different populations. Latitude and longitude had significant inverse relationship with organic acids. However, altitude did not affect the physico-chemical properties. The variability in the studied traits appeared to be geographically structured and would be mainly controlled genetically. The natural variation in wild fruit populations had given great opportunity to understand the variability in physical and chemical properties of fruit and response to biotic and abiotic stresses.